2007
DOI: 10.1117/12.698977
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide impurity level location in GaN, AlN, and ZnO

Abstract: A method that has proven succesful in locating the energy levels of divalent and trivalent lanthanide ions (Ce, Pr,..., Eu,...Yb, Lu) in wide band gap inorganic compounds like YPO 4 and CaF 2 is applied to locate lanthanide levels in the wideband semiconductors GaN, AlN, their solid solutions Al x Ga 1-x N, and ZnO. The proposed schemes provide a description of relevant optical and luminescence properties of these lanthanide doped semiconductors. Especially, the relation between thermal quenching of Tb 3+ emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
12
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 29 publications
6
12
0
1
Order By: Relevance
“…The trends on the splitting between the HO and LU 4f-related RE levels are in good agreement with that model [27]. As discussed in the previous paragraph for Gd in GaN, Gd in ZnO also has an U value that is considerably smaller than the respective HO-LU energy splitting, as shown in fig.…”
Section: (B)supporting
confidence: 75%
See 3 more Smart Citations
“…The trends on the splitting between the HO and LU 4f-related RE levels are in good agreement with that model [27]. As discussed in the previous paragraph for Gd in GaN, Gd in ZnO also has an U value that is considerably smaller than the respective HO-LU energy splitting, as shown in fig.…”
Section: (B)supporting
confidence: 75%
“…Our results showed otherwise, they indicated that all RE impurities in ZnO stay in a 3+ oxidation state, as for the RE impurities in GaN. Such results in ZnO are fully consistent with assumptions used in the phenomenological model [27]. For a RE in ZnO to achieve such oxidation state, it donates two electrons to stabilize the binding with the oxygen neighboring atoms, while the third electron populates the bottom of the ZnO conduction band.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…The error is assumed to be systematic for each lanthanide and on the order of 0.5 eV [58]. It needs to be mentioned here that a similar lanthanide energy level scheme for a compound with comparable band gap, namely GaN (band gap 3.42 eV), was published [55,59]. Dorenbos had already published numerous papers connected to such energy diagrams for various compounds, for example YPO 4 [54], Y 2 O 3 , CaBPO 5 , KCl [60], CaF 2 [54], Al x Ga 1 - x N [55] and therefore following his procedure was also considered applicable for our KLuS 2 ternary sulfide.…”
Section: Resultsmentioning
confidence: 99%